Análise de similaridade entre sequências dos genes do HIV-1 e o Genoma Humano - Galinskas, Juliana [UNIFESP] (2010)
It is possible that viral genes have cellular origins. They may have been gathered during evolution, and each one may correspond to a distinct origin. The similarity between genetic sequences suggest homology and, therefore, an evolutive relationship. The present study aimed at identifying region with similarity, with significant statistic support, between the human and the HIV-1 genome through the comparative analysis between DNA sequences using the BLAST program. It is also our purpose to develop a methodology which allows the comparison between genetic sequences of diverse organisms, quantifying the similarity. Thus, to carry it through, we use the BLASTn software (2.2.20 version) and a local database of human chromosomes. Python (5.1.30 version) is used for sequence processing and the data analysis is made using the SQL (Structured Query Language). The human genome is compared to sequences from: HIV-1 genes, Tobbaco Mosaic Virus genes (negative non-biologic control), chromosomes motifs of Macaca mulatta (positive biologic control) and random sequences (negative non-biologic control). We find differences between all the HIV-1 genes and the LTR region. Some genes show more similarity with the human genome than others, according to the curve fitting analysis. When analyzing the curve obtained at very low E-values, it is observed that all HIV-1 genes are well represented by a non-linear curve fitting y = a0 . xa1 where a0 and a1 are parameters obtained numerically. As a result, the method is validated using the data from the genome of Macaca mulatta for which a high level of similarity with the human genome is observed. Based on this validation, it is possible to form three distinct groups of genes from HIV-1 according to the a1 value where: the env, gag, nef, pol, rev, tat and vif genes have identical a1 values; the vpr gene a very low a1 value; and the vpu a a1 higher value.